2014
DOI: 10.1097/qai.0000000000000273
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Cognitive Impairment in UK HIV-Positive Men Who Have Sex With Men

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…The significance of ANI has been questioned in the NeuroAIDS field since the publication of the Frascati definition. The real implications of ANI have been criticised by some authors, implying that, as it is now defined, it falsely inflates the prevalence rate [39]. In fact, 10% (3) of our healthy controls had criteria of ANI after completing cognitive testing.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The significance of ANI has been questioned in the NeuroAIDS field since the publication of the Frascati definition. The real implications of ANI have been criticised by some authors, implying that, as it is now defined, it falsely inflates the prevalence rate [39]. In fact, 10% (3) of our healthy controls had criteria of ANI after completing cognitive testing.…”
Section: Discussionmentioning
confidence: 93%
“…The prevalence of HAND varies substantially depending on the consulted source [1, 3943]. In recent literature, prevalence ranged from 69% in a wider cohort of people living with HIV in French-speaking Switzerland [41] to 21% in a more specific cohort of urban men who have sex with men in the London metropolitan area [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first published results from this study were based on 248 MSM recruited at the two UK clinics involved (see McDonnell et al 42 ). The results indicated that the prevalence of NCI in HIV-positive MSM in the UK was 21%, 31% or 40% depending on the standardised scoring criteria used.…”
Section: The Antiretrovirals Sexual Transmission Risk and Attitudes mentioning
confidence: 99%
“…In the Cognitive Impairment in People with HIV in the European Region (CIPHER) study of 248 healthy HIV-infected participants (mean CD4+ count of 550 cells, 88% on cART), investigators found no difference in the frequency of cognitive impairment compared to demographically similar HIV-uninfected controls [27]. These data should be interpreted with caution given such a limited sample of controls (n=45) of which nearly one-third met criteria for cognitive impairment and the sample selection from regular clinic attendees.…”
Section: Introductionmentioning
confidence: 99%